EFEKTIVITAS KURSUS CALON PENGANTIN TERHADAP KESIAPAN CALON PENGANTIN PERSPEKTIF MASLAHAH MURSALAH - Angraeni, Anggi; Patimah; Mustafa, Zulas'ari (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
This study examines the effectiveness of the premarital course in preparing prospective brides and grooms from the perspective of maslahah mursalah (a case study at the Office of Religious Affairs (KUA) in Bantaeng Subdistrict, Bantaeng Regency). The main focus of this research includes: 1) the effective is the implementation of the premarital course at the KUA of Bantaeng Subdistrict, and the contribution of this course to the readiness of prospective couples from the perspective of maslahah mursalah. This study employs a qualitative approach with field research as its methodology. The primary data sources are the KUA officers and participants of the premarital course (Suscatin). Data collection techniques include observation, interviews, and documentation. The findings indicate that the premarital course at the KUA of Bantaeng Subdistrict is effective, as evidenced by the positive responses of Suscatin participants and the absence of divorce cases among couples who attended the course. This study recommends that Suscatin be established as a substantive and administrative requirement, rather than a mere formality. Additionally, the KUA should enhance the socialization of the Suscatin program to the community and strengthen collaboration with relevant experts to support the implementation of the premarital course.